Mineral Particles Modulate Osteo-chondrogenic Differentiation of Embryonic Stem Cell Aggregates - Wang, Yun (Acta Biomater, 2015)
Pluripotent stem cell aggregates offer an attractive approach to emulate embryonic morphogenesis and skeletal development. Calcium phosphate (CaP) based biomaterials have been shown to promote bone healing due to their osteoconductive and potential osteoinductive properties. In this study, we hypothesized that incorporation of CaP-coated hydroxyapatite mineral particles (MPs) within murine embryonic stem cell (ESC) aggregates could promote osteo-chondrogenic differentiation. Our results demonstrated that MP alone dose-dependently promoted the gene expression of chondrogenic and early osteogenic markers. In combination with soluble osteoinductive cues, MPs enhanced the hypertrophic and osteogenic phenotype, and mineralization of ESC aggregates. Additionally, MPs dose-dependently reduced ESC pluripotency and thereby decreased the size of teratomas derived from MP-incorporated ESC aggregates in vivo. Our data suggested a novel yet simple means of using mineral particles to control stem cell fate and create an osteochondral niche for skeletal tissue engineering applications.